Assessing Students’ Speaking Using the Theory of Linguistic Competence - Roza, Delvia; Anita, Fenny (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
Grammar is still considered the most problem experienced by Indonesian native speaker in speaking English, especially those who are preparing for the IELTS test. Thus, this study aimed to assess five students’ speaking performance to determine their linguistic competence in speaking. This study employed qualitative descriptive design with a case study method. The participants were five students of an IELTS course. The spoken data was collected by face-to-face interview, transcribed, and analysed using the theory of linguistic competence proposed by Celce-Murcia et al. The parameters used in the study were the noun clause and adjective clause (syntax), the subject and verb agreements (morphology), and the pronoun references (lexicon). It was found that the students had several weaknesses in performing subject and verb agreement as well as pronoun references, while they found no difficulties in using adjective and noun clauses. A ‘lexical sophistication’ strategy can be implemented to improve the students’ grammar in speaking by playing roles as IELTS examiners and test takers.